Design estratégico e a experiência IPA-Metodista: uma discussão entre o sistema produto proposto e percebido - Montaña, Misael Paulo (Universidade do Vale do Rio dos Sinos, 2010)
This study developed, through concepts that belong to the strategic design and experience design perspectives, an analysis about the educational institution IPA-Methodist ́s Product-system through the counterpoint between its audiences perceptions and propositions regarding the product-system. It starts from the idea that in order to understand the academic life experiences it is important to go beyond what the education institution can imagine or even what the pupils say on it: it implies in the search for a constructive way where both canact and project its experiences of integrated form. To reach these objectives with the support of the concepts mentioned above, some tools from the strategic design perspective such as moodboards and product-system maps were used, together with the logic of the study of case and the interviews in depth with the different institution ́s publics. The findings can help to improve the contextualization of this reality regarding the relation between institutions of higher education and academic community, since it was observed the richness and complexity of this experiential process that needs further exploration, where it was perceived not only the necessity of better alignment from those who proposes the product-system but also the discussing process with the institution ́s consumers as a possibility of developing new ideas for this product-system.
Keywords: Instituição de ensino; Sistema-produto; Design de experiência; Education institution; System-product; Design of experienc; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial